e·Chinese Tools: The Pan Gu of Digital Resources for Teaching and Learning Chinese as a Foreign Language - Rovira-Esteva, Sara; Vargas-Urpí, Mireia; Casas-Tost, Helena; Paoliello, Antonio (Sinología hispánica. China Studies Review, 2024)
Nowadays the use of technologies is deeply embedded in the teaching and learning of foreign languages. Therefore, students and teachers are compelled to continuously update their digital skills. Moreover, the need for online teaching has been spurred by the COVID pandemics, which has posed new challenges in this regard. When searching for online tools, one of the main difficulties is the vast amount and disparity of resources available to both teachers and students, who often feel overwhelmed due to the lack of time or assessment criteria. In such cases, the potential of existing resources remains largely unexplored. In this context, we developed an online open access database of digital resources for Teaching and Learning Chinese as a Foreign Language. This ongoing digital project includes a collection of metadata to satisfy users with different profiles and needs. The database structure and resources’ tagging were designed through a dialogical process among all team members. Additionally, all resources are thoroughly analysed and described by a minimum of two researchers to guarantee overall consistency and quality. In sum, we set up an open access multilingual (Catalan, Spanish, English and Chinese) and dynamic website, which can be useful for both teachers and learners who, in turn, will be able to enrich it through different types of feedback. Through this paper, we present the rationale behind the database as well as the making of this project. Additionally, the paper aims to explain the database’s main features and to offer a quantitative overview of the existing resources. Lastly, through a close reading of the collected data, we will reflect on the existing offer, the gaps, the new trends as well as on how to fruitfully use ICTs to develop new educational resources in the field of TCFL.